2013
DOI: 10.1136/injuryprev-2012-040717
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pedestrian countdown signals on pedestrian-motor vehicle collisions: a reanalysis of data from a quasi-experimental study

Abstract: ObjectiveTo perform a more sophisticated analysis of previously published data that advances the understanding of the efficacy of pedestrian countdown signal (PCS) installation on pedestrian-motor vehicle collisions (PMVCs), in the city of Toronto, Canada.MethodsThis is an updated analysis of the same dataset from Camden et al. A quasi-experimental design was used to evaluate the effect of PCS on PMVC. A Poisson regression analysis, using a one-group comparison of PMVC, pre-PCS installation to post-PCS install… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…The body of peer-reviewed literature examining the effect of PCS on MVCs is limited and conflicting in its conclusions. Our findings are consistent with our recent publication by Richmond et al (2013) of pedestrian motor vehicle collisions with these same intersections and countdown signals. This study demonstrated a 26% increase in the rate of pedestrian motor vehicle collisions, pre-to post-PCS installation (Richmond et al, 2013).…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…The body of peer-reviewed literature examining the effect of PCS on MVCs is limited and conflicting in its conclusions. Our findings are consistent with our recent publication by Richmond et al (2013) of pedestrian motor vehicle collisions with these same intersections and countdown signals. This study demonstrated a 26% increase in the rate of pedestrian motor vehicle collisions, pre-to post-PCS installation (Richmond et al, 2013).…”
Section: Discussionsupporting
confidence: 96%
“…Our findings are consistent with our recent publication by Richmond et al (2013) of pedestrian motor vehicle collisions with these same intersections and countdown signals. This study demonstrated a 26% increase in the rate of pedestrian motor vehicle collisions, pre-to post-PCS installation (Richmond et al, 2013). Our findings, however, contradict results published by Pulugurtha et al (2010) who found a decrease in MVCs after installation of PCS.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…These have likely decreased child pedestrian versus auto events. While data are conflicting about the utility of pedestrian countdown signals as an injury prevention strategy, in 2006 Chicago regulated that all new pedestrian signals and all those needing repair be done with countdown signals Markowitz et al, 2006;Federal Highway Administration, 2008;Richmond et al, 2013).…”
Section: Influence Of Traffic Technology Changes Personal Electronicmentioning
confidence: 98%
“…It also corresponds to differences in road-user behavior regarding safety, and especially motorists' consideration for pedestrians (or cyclists) with whom they need to share the road. In all countries, pedestrians injured in road crashes are mainly hit by motor vehicles, and most often by passenger cars (Alhajyaseen et al 2013;Pulugurtha and Sambhara 2011;Richmond et al 2014a;Richmond et al 2014b). The interest of developing active and passive safety devices in cars is clear (Zegeer and Bushell 2012).…”
Section: Introductionmentioning
confidence: 99%